A new species and new records of Downeshelea Wirth & Grogan in Neotropical Mexico (Diptera: Ceratopogonidae) - Huerta, Herón; Felippe-Bauer, Maria Luiza; Spinelli, Gustavo R. (Zootaxa, 2012)
In the revision of the Ceratopogonini of the World, Wirth & Grogan (1988) placed the species of the Monohelea multilineata group in the new genus Downeshelea, which includes 33 species (Borkent, 2011), most of them known from the New World. Borkent and Spinelli (2000, 2007) listed 18 species from the Neotropical Region and Felippe-Bauer and Silva (2008) subsequently described D. oliveirai Felippe-Bauer from northern Brazil. From Mexico, only D. multilineata (Lutz) and D. panamensis (Lane & Wirth) have been reported.